Ultra-thin film composite mixed matrix membranes incorporating iron(iii)–dopamine nanoparticles for CO2 separation. Issue 15 (1st April 2016) - Kim, Jinguk; Fu, Qiang; Scofield, Joel M. P.; Kentish, Sandra E.; Qiao, Greg G.
Abstract : A novel ultra-thin film composite mixed matrix membrane consisting of a polyethylene glycol-based CO2 selective layer incorporating FeDA nanoparticles has been developed through a newly developed, one step nano-coating approach, namely CAP-ATRP. Abstract : Iron dopamine nanoparticles (FeDA NPs) are incorporated into a nanoscale thick polyethylene glycol (PEG) matrix for the first time, to form ultra-thin film composite mixed matrix membranes (UTFC-MMMs) via a recently developed continuous assembly of polymers (CAP) nanotechnology. The FeDA NPs are prepared by in situ nano-complexation between Fe 3+ and DA and have a particle size that can be varied from 3 to 74 nanometers by adjusting the molar ratio of DA to Fe 3+ ion. The cross-linked selective layer with sub 100 nanometer thickness is prepared by atom transfer radical polymerisation of a mixture of PEG macrocross-linkers and FeDA NPs on top of a highly permeable poly(dimethyl siloxane) (PDMS) prelayer, which is spin-coated onto a porous polyacrylonitrile (PAN) substrate. The incorporation of the FeDA NPs within the PEG-based selective layer is confirmed by XPS analysis. The UTFC-MMMs (thickness: ∼45 nm) formed present excellent gas separation performance with a CO2 permeance of ∼1200 GPU (1 GPU = 10 −6 cm 3 (STP) cm −2 s −1 cmHg −1 ) and an enhanced CO2 /N2 selectivity of over 35, which is the best performance for UTFC membranes in the reported literature.